Understanding the influence of static magnetic field assisted freezing on texture properties and digestibility of rice in beef fillet fried rice - Zhilu Ai; Jun Zhang; Shuaishuai Zheng; Chao Xu; Zhen Li; Zhili Pan; Yong Yang (Applied Food Research)
In order to further expand the application range of static magnetic field assisted freezing technology, the effects of static magnetic field assisted freezing on the texture properties and digestibility of rice in beef fillet fried rice were studied in this paper. The static magnetic field accelerated the freezing rate and shortened the phase transition time of beef fillet fried rice, and the effect of 2 mT magnetic field intensity was better than that of 1 mT. Specifically, compared with the RF group, the freezing time in the SMF-2 group decreased by 24.97 %. With the acceleration of freezing speed, the expansion pressure generated by ice crystal formation gradually reduced the damage to the structure of rice, making its ability to bind water stronger and reducing the rearrangement of starch molecules. Among them, compared with the RF group, the relative crystallinity of the SMF-2 group decreased by 2.04 %, and the R1047/1022 value of the SMF-2 group also reduced by 4.47 %. Alleviation of starch retrogradation by static magnetic field inhibited the increase in hardness and chewiness of rice, as well as the decrease in adhesiveness and digestive rate. In conclusion, static magnetic field assisted freezing can improve the texture quality and digestibility of rice in frozen beef fillet fried rice. The research results of this article provide further support for the application of static magnetic field assisted freezing technology in prefabricated food dishes.